(3GdeYGdLGJ GdafjI dYfGUQ GdehSjbi GdTYHjI GdCSHGfjI aj GdbQf GdYTQjf ef NdGd CYeGd HYV GdeDdajf GdCSHGf (B= s Artistic treatments of the Spanish folk music during the twentieth century through the works of some Spanish composers - (3gHg EHQGgje YRhR eMeOs; (3CSGeI YHOGdedc CHGghQ (B: s; (3eMeO GdeYJUe GdNVQi (B: s ((3GdbGgQI (B: s (3gHg EHQGgje YRhR eMeO (B: s, 2010)
(3jJfGhd gPG GdHMK GdeYGdLGJ GdafjI dYfGUQ GdehSjbi GdTYHjI YfO HYV GdeDdajf GdCSHGf aj GdbQf GdYTQjf (B((3YjfI GdHMK(B) (3HGdOQGSI h GdJMdjd (B: (3h Pdc ddhUhd Edi CSdhH GdeYGdLI GdafjI YfO cd ef eGfhjd Oj aGjG h NhGcjf JhQjfG h aOQjch eheHh deDdaGJ GdHjGfh(B. (3HYO GdJYQa Ydi CSdhH GdeYGdLGJ GdafjI dYfGUQ GdehSjbi GdTYHjI GdCSHGfjI aj GdbQf GdYTQjf ef NdGd YjfI GdHMK GdefJbGg ef CYeGd HYV GdeDdajf GdCSHGf(B. (3bGeJ GdHGMKI HOQGSI h JMdjd KeGfjI ebWhYGJ dBdI GdHjGfh (B: (3h ebWhYI hGMOI ddChQcSJQG (B((3GdLRA GdNGU HBdI GdJTjddh(B) : (3HhGbY KdGK ebWhYGJ dcd ef GdeDda eGfhjd Oj aGjG (B: (3h GdeDda NhGcjf JhQjfG (B: (3h GdeDda aOQjch eheHhs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI GdfhYjI (B- (3bSe GdJQHjI GdehSjbjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdehSjbi GdTYHjI GdCSHGfjIs; (3GdehSjbi ai GdbQf GdYTQjfs; (3GdehSjbjjf GdCSHGfs